Novel endoscopic gastric purse-string suture device for weight management in a porcine model (with video) - Yiyu Qiao; Shuqian Hu; Wei Shen; Airong Tang; Xueting Zhang; Hanqing Zhang; Min Min; Yan Liu (Endoscopy International Open)
Obesity is a global health issue. Traditional treatment modalities such as lifestyle modifications, pharmacological interventions, and bariatric surgery often present various limitations. Recently, endoscopic bariatric and metabolic therapies (EBMTs) have emerged as promising minimally invasive approaches for weight management. These therapies reduce gastric volume and energy intake, prolong gastric emptying, and regulate hormones associated with satiety. This study evaluated endoscopic gastric purse-string suturing (EGPSS), a novel endoscopic procedure designed to reduce gastric fundus volume while minimizing associated risks. We assessed its feasibility and efficacy in a porcine model in terms of histological, physiological, and metabolic outcomes. The results suggest that EGPSS offers a viable option for metabolic control.